Contribution of Sports and Games to Changing Students’ Social Behaviour: A Focus on Selected Public Secondary Schools in Temeke Municipality, Tanzania - Leah R. Masaba; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
This study aimed to assess the contribution of sports and games in changing student behavior in a case of a selected public secondary school in Temeke Municipality. Specifically, the study aimed to investigate students’ preferred sports and games in relation to the behavioral change benefits of selected games, e.g., football, on teamwork enhancement among secondary school students and to determine the relationship between sports and games and academic activities. The study employed a mixed research approach and a sequential exploratory research design. Four hundred and twenty (420) participants, including sports and games teachers, students and schools heads, were sampled and exposed to question items on the interviews, documentary sources, questionnaires, and focus group discussions. The results reveal that sports activities play a significant role in fostering physical fitness and emotional well-being among children and adolescents. Engaging in sports activities elicits a range of favourable physiological adaptations, primarily enhancing the cardiovascular and muscular systems. In addition, engagement in sporting activities was found to be positively related to psychological factors related to mental well-being while also facilitating the active integration of children and adolescents into society and overall academic performance. Thus, sports teachers and educators must create environments in the playing fields that support ideal notions of ethics, moral reasoning, character and sportsmanship. In doing so, the sports teachers should have the intention of building character when they are engajing with students. This means that without intentions from students and sports teachers themselves, sports cannot build up character.